PENERAPAN PERMAINAN TRADISIONAL KERAPAN SAPI UNTUK MENINGKATKAN MOTORIK KASAR PESERTA DIDIK KELAS III SD NENGRI PAKIS 1/368 SURABAYA - Agnes Diona Febriyanti; Agung Bayu Aji; Agung Prasetya; Agus Prasetiyo; Agustia Indra Wahyu; Marsudianto; Fifukha Dwi Khory (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This Classroom Action Research was conducted with the aim of determining the improvement of gross motor skills in children by implementing the bull racing game through the PTK classroom action research method in grade III students at SD NENGRI PAKIS 1/368 SURABAYA, Jl Pakis Tirtosari VIII/14, Sawahan District. This study used two cycles, namely cycle 1 and cycle 2. The data collection techniques used were tests, documentation, and observation. This study used the PTK method to improve gross motor skills in children in the bull racing game of grade III students at SD NENGRI PAKIS 1/368 SURABAYA, Jl Pakis Tirtosari VIII/14, Sawahan District. From the results of the study, there was an increase in the results of motor tests in children from cycle I to cycle II, both from the improvement of gross motor skills in children. The completion of learning outcomes in cycle I was (63%) and in cycle II (96%), so that the increase from cycle I to cycle II was (33%).